Pengaruh Keputusan Investasi, Keputusan Pendaaan Dan Tingkat Suku Bunga Terhadap Nilai Perusahaan (studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2017-2019) - Hanindya Indriatitisari; Budi Wahono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research was conducted with the aim of analyzing the effect of investment decisions, funding decisions and interest rates on firm value. The population used in this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample selection in this study using purposive sampling technique. Companies included in the research criteria consisted of 11 companies for 3 years. This research uses financial statement data from manufacturing companies listed on the IDX. The data analysis technique in this study used normality test, classic assumption test, multiple linear regression test and hypothesis testing with the tools of the SPSS (Statistics Product and Service Solutions) application.The measuring instrument used to measure investment decisions is the Price Earning Ratio (PER), for decisions is the Debt to Equity Ratio (DER), the interest rate uses the reference interest rate that has been set by the government and for the company value is the Price to Book Value (PBV). ). The results of this value are (1) investment decisions, decisions and interest rates that affect the value of the firm, (2) investment decisions partially on the effect on firm value, (3) decisions taken partially do not affect firm value, (4) )) the interest rate has no effect on firm value. Keywords: investment decisions, decisions, interest rates, firm value